Seasonality in Holocene Temperature Reconstructions in Southwestern China. Issue 1 (21st January 2021) - Sun, Xiaoshuang; Zhao, Cheng; Zhang, Can; Feng, Xiaoping; Yan, Tianlong; Yang, Xiangdong; Shen, Ji
Abstract: Reconstructions of global surface temperature, dominated by records from the northern extratropics, show an apparent Holocene cooling trend after the early Holocene climatic optimum. However, model simulations suggest a global warming Holocene tendency. This "Holocene temperature conundrum" may be caused by the seasonal bias of paleotemperature proxies. Here we report a quantitative Holocene record with ∼100‐year resolution based on branched glycerol dialkyl glycerol tetraethers from an alpine lake in southwestern China. Our reconstructed Holocene temperature record displays a steady long‐term trend without distinct cooling or warming changes. Based on the temperature values and their evolution over time, our reconstruction is interpreted to present temperature changes in ice‐free seasons from March to November. Unlike the often‐documented Holocene cooling of regional summer temperatures driven by boreal summer insolation, this observed trend in our reconstructed temperatures is probably caused by slightly decreasing local ice‐free season insolation and somewhat compensated by increasing atmospheric greenhouse gas concentrations. Our results demonstrate that the climatic drivers of ice‐free season and summer temperature changes could be different and highlight the significance of elucidating the seasonality of proxies before using them for paleoclimate reconstructions. Plain Language Summary: Reconstruction of Holocene climate change provides an important basis for understanding long‐term climate variability over the last 13.1 kyr and provides context for better projecting future climate change. The gradual Holocene cooling documented by many of the current proxy‐based temperature records obviously contradicts the overall warming tendency simulated by climatic models, which limits our understanding of the driving mechanism of Holocene temperature change. Here, we quantitatively reconstruct a Holocene temperature record from an alpine lake in southwestern China. We interpret this record is relation to the ice‐free season (March to November) and find that it does not show the distinct cooling or warming trend for the Holocene shown in many previous paleoclimate reconstructions and model simulations. We infer that this observed Holocene temperature trend has been driven by the interplay of subtle declines in local ice‐free season insolation and slightly increasing atmospheric greenhouse gas concentrations. This is quite different from the previously identified Holocene summer cooling driven by a distinct decline in local summer insolation and the Holocene winter warming caused by increasing insolation. This finding suggests the importance of considering the seasonality of proxies before using them for quantitative temperature reconstructions and inferring paleoclimate mechanisms. Key Points: Holocene quantitative temperature reconstruction for an alpine lake in southwestern China was performed No obvious warming or cooling trend was observed in the new Holocene temperature record Considering seasonal influences on the proxy response is required for Holocene temperature interpretation